Correction: Correlation between the electronic/local structure and CO-oxidation activity of PdxRu1−x alloy nanoparticles. Issue 2 (23rd January 2019) - Song, Chulho; Tayal, Akhil; Seo, Okkyun; Kim, Jaemyung; Chen, Yanna; Hiroi, Satoshi; Kumara, L. S. R.; Kusada, Kohei; Kobayashi, Hirokazu; Kitagawa, Hiroshi; Sakata, Osami
Abstract : Correction for 'Correlation between the electronic/local structure and CO-oxidation activity of Pd x Ru1− x alloy nanoparticles' by Chulho Song et al., Nanoscale Adv., 2019, DOI: 10.1039/c8na00305j.